Human biology - Mader, Sylvia S (McGraw-Hill, 2014)
To accomplish the goal of improving scientific literacy, while establishing a foundation of knowledge in human biology and physiology, Human Biology integrates a tested, traditional learning system with modern digital and pedagogical approaches designed to stimulate and engage today student.